UPData: a data curation experiment at U. Porto using DSpace - João Rocha da Silva (2011)
UPData is a scientific data curation experiment currentlyunder development at University of Porto which aims todetermine the main digital preservation needs of several researchgroups at the university. In the course of the experiment,eight datasets have been collected from diversescientific domains. After conducting several interviews withresearchers working at U.Porto, we have concluded that fromtheir point of view, flexible data access is the most valuedcapability when analysing a preservation solution and thatoffering such access it is the best way to involve them inthe preservation workflow. We propose an extension to theDSpace repository platform to complement it with data curationcapabilities. In the proposed solution, the system ingestsExcel spreadsheets containing scientific data and translatesthem into XML documents which can then be queriedvia automatically generated XQuery statements. Researchersuse a search webpage designed for displaying deposited dataand applying various filters to it, retrieving the parts theyneed without having to scan each file. The collected datasetswill be used as test cases for data deposit, and also to evaluatethe effort required by the curation procedure.